Unggul Bersaing Batik Jambi: Studi Batik Berkah Jambi - Titin Agustin Nengsih; Ayu Minarsi; Muhammad Ismail (J-MAS (Jurnal Manajemen dan Sains), 2021)
The Jambi Batik Industry is currently experiencing a decline because a lot of the Jambi batik motifs circulating in the market are mostly supplied from the Java region. The effect of this condition is the original Jambi batik craftsmen get sluggishness in producing Batik. The purpose of this research is to determine the factors that influence Jambi batik to be competitive, especially Batik Berkah Jambi City. The predictors variables used are product innovation, product quality, and social media. The research method uses quantitative methods by obtaining primary data from a questionnaire by taking 100 respondents and secondary data from interviews with the gallery owner of Batik Berkah Jambi. The results show that the variables of product innovation, product quality, and social media have a significant effect on the competitive advantage of Jambi Batik. Furthermore, product innovation, product quality, and social media also have a significant effect on competitive advantage at Batik Berkah Jambi City with a coefficient of determination is 57.1% and the remaining 42.9% is influenced by other variables.